Notary Responsibility for Employee Health Insurance (Study in Mataram City) - Suryawati, Dyah Eka; Muhaimin,; Risnain, Muh. (International Journal of Scientific Research and Management (IJSRM), 2019)
The title of this journal writing is the Notary's responsibility for Employee Health Insurance. The purpose of writing this journal is to (1) To analyze the arrangement of Notary's responsibility towards the employee's Health Insurance registration according to positive law, (2) To explain and analyze the application of sanctions for Notaries who have not included their employees in Health Insurance. This study uses a normative - empirical approach. The data used are primary data and secondary data. The data obtained were analyzed qualitatively and then presented in descriptive descriptions. The research results lead to a conclusion that: (1) Every company such as a Notary office is an employer, in Law No. 24 of 2011 Article 15 paragraph (1) employers are required to gradually register themselves and their workers as BPJS participants, (2) Mechanism for imposing administrative sanctions for companies that have not become participants of BPJS Kesehatan Insurance are written warnings, fines and do not receive certain public services.